The effect of a swivel seat on performance, kinematics and body rotation during maximal intensity on-ergometer kayaking - López-Plaza, D.; Alacid, F.; Willmott, A. P. (Sports Biomechanics, 2025)
In recent years, physiological investigations suggested that a kayak seat able to rotate in the horizontal plane (swivel seat) may improve performance, but kinematic data are limited. The aim of this study was to investigate the effect of the swivel seat on kinematics and performance during sprint paddling on an ergometer. Nine experienced kayakers volunteered for this study and each completed two maximal trials of 30 s on the ergometer, one with the swivel seat and the other with a fixed seat. Three-dimensional motion analysis and performance data were collected at 200 Hz during the central 10 s of each trial. The use of the swivel seat was observed to improve performance through a significant increase in peak fly-wheel RPM (p = 0.033) and paddle antero-posterior displacement (p = 0.015) and a significant decrease in right side paddle recovery time (p = 0.043). In conclusion, the use of the swivel seat was associated with kinematic changes that improved performance and decreased the risk of excessive spine rotation. These results offer new insights into understanding the implications of swivel seat use for the dynamics of kayaking.